Korelasi Durasi Pemberian ASI terhadap Klasifikasi Derajat Stunting pada Balita - Astrid Wiba Susanti; Iis Hanifah; Suhartin (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
Stunting is a chronic nutritional problem that remains a serious challenge to child health because it is associated with impaired physical growth, cognitive development, and the quality of human resources in the future. This condition is influenced by inadequate nutritional intake, particularly during the first 1,000 days of life, which plays a critical role in determining the quality of child growth. Exclusive breastfeeding is considered an important factor that contributes to meeting nutritional needs and strengthening the immune system of children. The research problem focuses on the relationship between breastfeeding practices and the degree of stunting among children aged 1-5 years in the working area of Sempol Community Health Center, Bondowoso Regency, in 2025. The study employed a quantitative approach using an analytic survey design with a population consisting of all stunted toddlers in the area. A sample of 75 respondents was selected using a proportionate stratified random sampling technique. Data were collected through questionnaires and observation sheets that assessed breastfeeding practices and the level of stunting based on the height-for-age (HFA) indicator. The results show that 72% of children received exclusive breastfeeding, while the remainder received partial breastfeeding or were not exclusively breastfed. The distribution of stunting severity indicates that 57.3% of children experienced mild stunting, 34.7% moderate stunting, and 8% severe stunting. The Chi-Square statistical test produced a p-value of 0.003 (p < 0.05), indicating a significant relationship between breastfeeding practices and the degree of stunting. These findings demonstrate that the nutritional quality and antibodies contained in breast milk play an important role in supporting optimal child height growth. The novelty of this study lies in its analysis of the relationship between breastfeeding practices and the severity of stunting within the specific context of a local community health center area that has rarely been examined in detail. The findings emphasize the importance of health education for mothers and strong family support to strengthen exclusive breastfeeding practices as a strategic effort to prevent stunting.